Perspectives of digital agriculture in diverse types of livestock supply chain systems. Making sense of uses and benefits - Baker, Derek; Jackson, Elizabeth L.; Cook, Simon (Frontiers in Veterinary Science, 2022)
Digital technology is being introduced to global agriculture in a wide variety of forms that are collectively known as digital agriculture. In this paper we provide opportunities and value propositions of how this is occurring in livestock production systems, with a consistent emphasis on technology relating to animal health, animal welfare and product quality for value creation. This is achieved by organizing individual accounts of digital agriculture in livestock systems according to four broad types – commodity-based; value seeking; subsistence and nature-based. Each type presents contrasting modes of value creation in downstream processing; as well as from the perspective of One Health. The ideal result of digital technology adoption is an equitable and substantial diversification of supply chains, increased monetization of animal product quality, and more sensitive management to meet customer demands and environmental threats. Such changes have a significance beyond the immediate value generated because they indicate endogenous growth in livestock systems, and may concern externalities imposed by the pursuit of purely commercial ends.